Hydration requirements with emetogenic chemotherapy: granisetron extended-release subcutaneous versus palonosetron. (2nd January 2018) - Vacirca, Jeffrey; Caruana, Dennis; Calcanes, George; Mosier, Michael; Boccia, Ralph; McBride, Ali
Aim: This retrospective analysis evaluated chemotherapy-induced nausea and vomiting (CINV)-related hydration needs with palonosetron or granisetron extended-release subcutaneous (GERSC), approved in 2016 for CINV prevention.Materials & methods: At a community practice, CINV-related hydration per chemotherapy cycle was determined following highly (HEC) or moderately emetogenic chemotherapy (MEC) and a guideline-recommended antiemetic regimen: NK-1 receptor antagonist, dexamethasone and either palonosetron only, GERSC only, or palonosetron switched to GERSC.Results: Palonosetron-only patients (n = 93) had a significantly higher mean (standard deviation) hydration rate (0.9 [1.1]) than GERSC-only patients (n = 91; 0.3 [0.6]; p < 0.0001). Switched patients' (n = 48) hydration rates were significantly higher in the HEC subgroup with palonosetron (0.7 [1.2]) versus GERSC (0.5 [1.0]; p = 0.028).Conclusion: GERSC in a three-drug antiemetic regimen may reduce hydration needs following HEC or MEC.